China's expanding influence in the V4 countries - Konečná, Mai (2023)
This Bachelor Thesis analyzes the relations between China and Central Eastern Europe, particularly the Visegrad Group, which consists of the Czech Republic, Hungary, Poland and Slovakia via the lens of normative power theory. This will be done by comparing the bilateral relations of individual member countries with China with the use of criteria of China's political, economic, and cultural presence. The aim of this thesis is to determine which country has the highest level of influence from China and to what extent China exerts its normative power in the Visegrad Group. The first part of the work will provide an overview of China’s foreign policy and to what extent it is a normative power. The second part will examine the political, economic, and cultural influence of China in each V4 country. The third part will compare these findings, and the work will conclude with which country is influenced by China the most.